Large PAMAM dendron induces formation of unusual P4332 mesophase in monoolein/water system - Kumar, Manoj; Patil, Naganath Ganapatarao; Ambade, Ashootosh V.; Kumaraswamy, Guruswamy (Langmuir, 2018)
Compact macromolecular dendrons have been shown to induce the formation of discontinuous inverse micellar assemblies with Fd3m symmetry in monoolein/water systems. Here, we demonstrate that a large PAMAM dendron (G5: fifth generation) induces the formation a very unusual mesophase with P4332 symmetry. This mesophase had previously been observed in monoolein/water systems only on addition of cytochrome C. The P4332 mesophase can be considered an intermediate phase between the bicontinuous Ia3d and discontinuous micellar mesophases. In this unusual phase, every third rod junction of the Ia3d mesophase is replaced with a spherical micelle. We present a detailed investigation of the phase behaviour of monoolein/water as a function of G5 concentration and temperature. Addition of 1% G5 in 85/15 monoolein/water system induces a transition from the L to Ia3d phase. Further increase in G5 concentration to above 2% induces the formation of the P4332 phase. Thus, incorporation of G5 yields a qualitatively different phase diagram when compared with incorporation of lower generation PAMAM dendrons (G2 – G4) in monoolein/water, where the reverse micellar Fd3m phase forms. PAMAM dendrons of all generations, G2 – G5, bear terminal amine groups that interact with the monoolein head group. The compact molecular architecture of the dendrons and these attractive interactions induce bending of the monoolein bilayer structure. For smaller dendrons, G2 – G4, this results in the formation of the Fd3m phase. However, the large size of the G5 dendron precludes this and a rare intermediate phase between the Ia3d and discontinuous micellar phase, the P4332 mesophase forms instead.